"Evaluación de la gestión del turismo comunitario en la comunidad de cachiviro, en el cantón Otavalo, Provincia de Imbabura, año 2020" - Amaguaña Burga, María Azucena (2020)
The present Research was carried out in order to evaluate the management of the tourist attraction of the community of Cachiviro, province of Imbabura. A situational diagnosis of the tourist attraction of the community was carried out, identifying tourist resources such as tourist facilities, tourist equipment, tourist activities. The level of satisfaction of tourists with the tourist services and activities offered by the community was also determined, where 270 surveys were applied to tourists who visited the tourist attraction, resulting in: 51% corresponds to the female gender, the majority being of adult visitors from 29 to 39 years old with a third level level of instruction; Most of the tourists are of Ecuadorian nationality, their form of mobilization is in their own car; the way they got information from this site was through word of mouth promotion; Among the most popular activities was the boat ride through the lagoon. In relation to the activities and facilities of the tourist attraction, more than 53% agree with the food service provided, on the contrary 58% of the tourists made it known that an efficient guiding service is necessary in the community; the parking service had a 38% acceptance rate, while 31% consider that the absence of vehicular signage is a problem, 36% of those surveyed agreed with the sale of handicrafts; The deteriorated appearance of the facilities such as the floating dock, the swing, the suspension bridge and the recreational areas caused negative criticism, but at the same time they have frequent use, there were opinions regarding the lack of information and signage for activities within the tourist attraction such as kayaking, hiking, sport fishing among others. Mr. José Peña, president of the Rey Mola Cocha association, was also interviewed, who stated that they do have plans to improve and expand the floating dock, but due to lack of knowledge to develop an architectural project, they have not done so; and this is the requirement requested by the prefecture and parish GAD to be able to present their support in the improvement of this attractiveness. Finally, a community tourism management plan was developed that includes product analysis, positive and negative factors, market research, potential client profile, competitor profile, and proposal for a plan for the protection of goods and services of the tourist attraction of the community. The Cachiviro, in order to improve the image of attractiveness to tourists. Keywords Tourist attraction, tourist resource, tourist equipment, tourist facilities, community